PKC-phosphorylation of Liprin-α3 triggers phase separation and controls presynaptic active zone structure - Javier Emperador-Melero (Nature Portfolio, 2021)
Liquid–liquid phase separation may be a mechanism for organizing the presynaptic nerve terminal. Here, the authors show that PKC-mediated phosphorylation of Liprin-α3 triggers phase separation in cell lines and modulates active zone structure and function in primary hippocampal neurons.